Variegated mud-loving beetles (Heteroceridae) of Russia and adjacent countries: genus Augyles of European part of Russia and Caucasus Region - Sazhnev, Alexey S. (Zootaxa, 2022)
This paper is the first inventory of the fauna of the variegated mud-loving beetles (Heteroceridae) of genus Augyles Schiødte, 1866 in the European part of Russia and Caucasus Region. It provides an annotated catalogue of eleven Augyles species currently recorded from European Russia and Caucasus Region, based on several collections and a critical evaluation of all earlier published records. All species are listed with a summary of their distribution in Caucasus, European Russia, and overall distribution. The species with new regional records (highlighted as asterisk) have a subsection “material examined” and/or remarks. Augyles hispidulus (Kiesenwetter, 1843) is reported for the first time from two federal subjects of Russia (Nizhniy Novgorod and Volgograd Oblasts). Augyles intermedius (Kiesenwetter, 1843) from Nizhniy Novgorod, Tambov and Tver Oblasts, and Augyles maritimus (Guérin-Méneville, 1844)—from Saratov Oblast of Russia are reported for the first time. The presence of Augyles pruinosus (Kiesenwetter, 1851) in the Azerbaijan is confirmed.